(untitled) (Progressive Agriculture, 2013)
A field study was conducted to test the efficacy of three insecticides viz. Dursban 20 EC, Decis 2.5 EC and Lebaycid 50 EC with three different doses @ 0.1%, 0.2% and 0.3% in controlling the Helicoverpa zea in maize (cv. BARI Hybrid Bhutta-5) at Entomology Field Laboratory, BAU, Mymensingh. The results showed that the lowest percent of cob infestation was 1.72%, 1.90% and 2.75% at 3 DAT, 7 DAT and 12 DAT in 0.3% Decis treated plots, respectively. The highest percent of cob infestation was observed in untreated plots. The lowest mean number of kernel damage (2.10) and yield loss (1.40 kg/ha) were found with 0.3% Decis 2.5 EC treated plots. The efficacy of insecticides were Decis 2.5 EC (0.3%) > Decis 2.5 EC (0.2%) > Dursban 20 EC (0.3%) > Lebaycid 50 EC (0.3%). The efficacy of all insecticides on cob infestation at different time intervals indicated that insecticidal toxicity decreases with the increasing time after application. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16848 Progress. Agric. 20(1 & 2): 43 47, 2009